C39 ECHOCARDIOGRAPHIC PREDICTORS OF MALIGNANT EVENTS IN ARRHYTHMIC MITRAL VALVE PROLAPSE POPULATION. (18th May 2022) - Desalvo, P; Vairo, A; Piroli, F; Gaiero, L; Fioravanti, F; De Lio, F; Bellettini, M; Montali, N; Alunni, G; Giustetto, C; De Ferrari, G
Abstract: Background: Bileaflet mitral valve prolapse (bMVP) has been linked to major arrhythmic events and sudden cardiac death (SCD). Solid evidence of consistent predictors of SCD in this setting is still lacking. Echocardiography is the best tool for the analysis of ventricle mechanics and for the correlation with electrical myocardial activation. The aim of this study was to find new predictors of malignant events within an arrhythmic MVP population. Methods: We conducted a retrospective comparative analysis, selecting 22 patients with bMVP with a high arrhythmic risk profile. 6 of them had a previous major arrhythmic event (5 aborted SCD, one cardiogenic syncope) and previously received ICD implantation (ICD–MVP), while 16 presented with a high arrhythmic burden without major events (A–MVP). All patients underwent transthoracic echocardiography in the last year. Each echocardiogram followed a specific protocol focused on mitral valve anatomy and ventricular contraction using 2D imaging, 3D imaging, tissue doppler imaging and speckle tracking analysis. Results: ICD–MVP group, compared with A–MVP group, presented a longer anterior leaflet (AML) length (28, 6 mm, IQR: 24, 1–31, 1 mm; vs 21, 4 mm, IQR: 20, 4–24, 0 mm; p = 0, 03), larger mitral valve annulus (MVA) indexed area (6, 88 cm2/m2, IQR 6, 27–7, 87 cm2/m2 vs 5, 44 cm2/m2, IQR: 4, 93–6, 15 cm2/m2, p = 0, 02), lower MVA anteroposterior diameter/AML length ratio (1, 24, IQR: 1, 21–1, 41 vs 1, 50, IQR 1, 32–1, 62; p = 0, 049), higher inferolateral basal S3 velocity (26 cm/s, IQR: 20, 8–29, 6 cm/s vs 14, 2 cm/s, IQR 10, 1–21, 3 cm/s; p = 0, 02) and a greater mechanical dispersion (MD) of the basal and mid–ventricular segments calculated with speckle tracking (128 ms, IQR: 125–131 ms; vs 58 ms, IQR 45–106 ms; p = 0, 03). Mitral regurgitation grading, instead, did not correlate with malignant events. Best predictors of malignant events were AML length and MD of basal and mid–ventricular segments. Cut–off values with highest sensibility and specificity above 80% were 26 mm for AML length and 122 ms for MD of basal and mid–ventricular segments. Logistic bivariate regression confirmed AML length as an independent predictor of malignant events (p = 0, 01), while MD of basal and mid–ventricular segments showed a trend toward significancy (p = 0, 07). Conclusion: Five parameters were found to be predictors of malignant events in a high–risk MVP population. AML length and MD of the basal and mid–ventricular segments presented the best predictive value.